Examining the Contributions of Trait Emotional Intelligence on Addiction Counselor Burnout - Gutierrez, Daniel (Journal of addictions & offender counseling, 2019)
The authors examined the contributions of emotional intelligence (EI) on burnout in addiction counselors. Results indicated that EI may act as a buffer against burnout, mitigating the impact of addiction counselor burnout. Recommendations are given for counselors, supervisors, and counselor training.